The Effect of Liquid Polyisoprene Rubber (LNR) on the Properties of Epoxy/Carbon Black Conductive Filler - Nurfarahin Juri (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
This researched was focus on the effect of different amount of LNR content on the properties of epoxy/LNR blend materials and to determine the effects of polyisoprene rubber and CB content on the properties of epoxy/LNR/CB conductive materials. In this study, epoxy/LNR and epoxy/LNR/CB composite were produced by mechanical mixing. The effect of LNR content on the mechanical, thermal, and electrical conductivity properties in epoxy/LNR were investigated.